2009
DOI: 10.1007/s00426-009-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

Late backward effects in the refractory period paradigm: effects of Task 2 execution on Task 1 performance

Abstract: The central bottleneck model assumes that in the psychological refractory paradigm, Task 1 performance is independent of Task 2 demands. Previous studies, however, have reported backward crosstalk effects of motor demands in Task 2 on Task 1 performance. These effects have been attributed to interference at the central level. The present study aimed to isolate more directly potential backward effects at the motor level. Therefore, in three experiments, movement distance in Task 2 was manipulated using a guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…First, there is strong evidence that motor processing cannot be performed in parallel when both tasks involve homologous limbs (Bratzke et al, 2008;Bratzke et al, 2009;De Jong, 1993;Ruiz Fernández & Ulrich, 2010;Ulrich et al, 2006). This assumption is supported by the present study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First, there is strong evidence that motor processing cannot be performed in parallel when both tasks involve homologous limbs (Bratzke et al, 2008;Bratzke et al, 2009;De Jong, 1993;Ruiz Fernández & Ulrich, 2010;Ulrich et al, 2006). This assumption is supported by the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Although the central bottleneck model provides a parsimonious account of several RT phenomena associated with the PRP paradigm, other research has indicated that processes prior to response selection (Johnston & McCann, 2006;Koch & Jolicoeur, 2007;Koch & Prinz, 2002) and motor processes (Bratzke et. al., 2008;Bratzke, Rolke, & Ulrich, 2009;;De Jong, 1993;Ruiz Fernández & Ulrich, 2010;Ulrich, 2006) can be subject to dual-task interference as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the results differed between the two experiments-that is, we only found evidence for an effect of R 2 −R 1 compatibility in the dual-task setting of the latter experiment. Nevertheless, the R 2 −R 1 compatibility effect in Experiment 2 clearly shows the possibility of T 2 interference independent from S 2 −R 1 compatibility, and this is generally in line with earlier findings demonstrating that T 1 -irrelevant characteristics of T 2 can still influence T 1 performance (e.g., Miller & Alderton, 2006;Ruiz Fernández & Ulrich, 2010). Like many earlier BCEs, the neutral-condition R 2 −R 1 compatibility effect seems to contradict pure RSB accounts of dual-task performance and to require an extension involving something like automatic response activation (Hommel, 1998).…”
Section: Implications For Response Selectionsupporting
confidence: 91%
“…The most-well known other type are compatibilitybased BCEs, which are likely caused by automatic response feature activation occurring in Task 2 (Hommel, 1998;Huestegge, Pieczykolan, & Janczyk, 2018;Janczyk, Pfister, Hommel, & Kunde, 2014;Janczyk et al, 2018;Lien & Proctor, 2000;Logan & Delheimer, 2001;Logan & Schulkind, 2000;Oriet, Tombu, & Jolicoeur, 2005;Schubert, Fischer, & Stelzel, 2008;Watter & Logan, 2006; see Durst & Janczyk, 2019, for a direct comparison). To allow for a more precise distinction of backward crosstalk phenomena, future studies should investigate to what extent the no-go BCE differs from still other types of BCEs, which seem to be based on motor processes in Task 1, Task 2, or even both tasks (Miller & Alderton, 2006;Ruiz Fernández & Ulrich, 2010).…”
Section: Relations To Other Phenomenamentioning
confidence: 99%